Influence of farmyard manure on retention and availability of nickel, zinc and lead in metal-contaminated calcareous loam soils - Aziz, Muhammad Abbas; Ahmad, Hamaad Raza; Corwin, Dennis L.; Sabir, Muhammad; Hakeem, Khalid Rehman; Öztürk, Münir (Journal of Environmental Engineering and Landscape Management, 2017)
Continuous irrigation of soils with untreated effluents can result in the accumulation and translocation of some metals in the soils and plants. Application of farmyard manure (FYM) to such soils may increase or decrease their availability and retention time. Calcareous soils contaminated with 100, 200, and 400mg kg–1 Ni, Zn, and Pb as chloride salts were used, and farmyard manure added (40g kg–1 for 90 days) with moisture contents at field capacity. Soil samples were drawn at 30 day intervals, and metals extracted with (AB-DTPA) C14H23NO3O10. With FYM application of 400 mg kg–1, Ni availability increased from 179 (day 30) to 240 mg kg–1(day 90); Zn from 163 (day 30) to 230 mg kg–1 (day 90), but, Pb decreased from 214 to 161 mg kg–1. FYM forms multi-dentate complex which greatly enhances the Ni and Zn solubility, and organic matter immobilizes Pb in the soil.